SISTEM REKRUTMEN DAN PEMBINAAN KOMPETENSI GURU SMK MUHAMMADIYAH PAGELARAN KECAMATAN PAGELARAN KABUPATEN PRINGSEWU - TITIN SARTINAH; Nur Khalis; Atik Rasdiani (UNISAN JURNAL, 2022)
:Recruitment is an effort made to obtain the human resources needed to fill certain vacant positions. With recruitment, it is hoped that high-quality job seekers will be aware of job opportunities. This is because recruitment is the first step in all stages. Therefore, this study took the title "Recruitment and Competency Development System for Teachers at SMK Muhammadiyah Pagelaran, Pagelaran District, Pringsewu Regency by taking a sample of 1 madrasa, namely SMK Muhammadiyah Pagelaran, Pagelaran District, Pringsewu Regency. The formulation of the problem in this study is "How is the Recruitment and Competency Development System for SMK Muhammadiyah Pagelaran Teachers, Pagelaran District, Pringsewu Regency?". This research uses the type of field research (Field Research), which aims to collect data or information about certain problems regarding the lives of the people who are the object of research. Data collection techniques in this study include: observation, interviews, and documentation. The data were analyzed with several analytical steps, namely data reduction, data presentation, and data verification or drawing conclusions. The conclusion from the results of this study is that the new teacher recruitment system at SMK Muhammadiyah Pagelaran, Pagelaran District, Pringsewu Regency is not good enough to include steps, namely presenting various laws or government regulations, foundation regulations relating to teacher recruitment regulations, establishing requirements for applying to become new teachers, establishing new teacher registration procedures, setting new teacher recruitment schedules, preparing facilities needed in the new teacher recruitment process, preparing rooms or places to enter new teacher applications, and test venues, distribute announcements of new teacher admissions, accept new teacher applications, select applicants, and evaluate recruitment. Keywords: Recruitment System, Teacher Competence Development